Pivotal Role of Seed Industry in Global Food Security in Current millennium - Vidyasagar, Parchuri (International Journal of Bio-resource and Stress Management, 2023)
When we are now feeling pride in living in a global village, global food security is a concern for all. Nutritional security has added a new dimension to food security. Food comes from plants directly and also from animals, which in turn are dependent on feed security based on plant products. Fuel security to meet energy crisis is a recent phenomenon, which also affects food security because a significant proportion of food crops are diverted to growing grains and biomass for bio-fuel production. Land area is not only limited, but is also being eroded by encroachment on agricultural lands for human habitation, setting up various industries and other infrastructure. Population is increasing at an alarming rate and arable land per caput for food security and other needs is inadequate to produce the needed quantum and quality of foods for the immense population that is further increasing day by day